IMPLEMENTASI PASAL 76 I DAN PASAL 88 UNDANG – UNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN UNDANG-UNDANG NO 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK DI KOTA DUMAI - Bayu Fauziah; Erdianto Erdianto; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Basically, children have the right to get special protection in order to grow and develop properly. In writing this thesis, the author tries to examine the implementation of Article 76 I and Article 88 of Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection in Dumai City.The purposes of writing this thesis are: first, to find out the implementation of Article 76I and Article 88 of Law Number 35 of 2014 concerning child protection for parents who employ children in the Dumai city area. Second, to find out the obstacles in implementing criminal sanctions in the Dumai City area for perpetrators who employ children in the Dumai City area and to find out what law enforcement efforts can do to overcome the obstacles to criminal application against perpetrators who employ children in the Dumai city area. The research method in this thesis uses a sociological legal research type, namely research that wants to see the correlation between law and society, so as to be able to reveal the effectiveness of law enforcement in society and identify unwritten laws that apply to society, so in this sociological legal research which is carried out At first, careful research is secondary data which is then continued with research on primary data in the field or on the community.Based on the results of the study, the first conclusion can be drawn that the existing legal protection system for child labor has not been implemented in real terms, criminals do not get strict legal action so that the reality of crime and deviant behavior is growing. Second, the obstacles faced by the government in implementing the crime on child protection against parents who employ children in the Dumai City area include weak law enforcement and supervision related to perpetrators who employ children, violations of the law are always carried out continuously or become a habit and are considered as a normal thing. and appropriate, the lack of community participation and understanding related to child labor violations and the weak economic condition of the community so that children are forced to work. And Efforts That Can Be Done In Implementing Crimes Regarding Child Protection Against Parents Who Employ Children in the Dumai City Area are socializing laws and regulations, holding routine patrols, coordinating and collaborating between relevant agencies or institutions in the field of child labor and in terms of law enforcement. In terms of quantity and quality, it is necessary to add personnel/officers so that officers can be more optimal in carrying out their duties.Keywords: Law Enforcement, Child Protection, Parents Who Employ Children